2022-RA-1127-ESGO The efficacy of MEK inhibitors in the treatment of low-grade serous ovarian cancers: a systematic review. (20th October 2022) - Kulkarni, Anjali; Cooke, Carly M; Fung-Kee-Fung, Michael; May, Taymaa; Zigras, Tiffany
Abstract : Introduction/Background: The low response rates to traditional systemic therapies prompts the need for novel therapies in the treatment of LGSC. LGSC tumors have demonstrated a high frequency of mutations in the MAPK cascade, which is targeted by MEKi. The primary objective of this systematic review was to assess the overall response rate (ORR) of LGSC to MEKi. Methodology: Pubmed, EMBASE, Medline and the Cochrane Database were searched from inception to March 2022. Inclusion criteria were studies assessing the treatment of LGSC in the primary or recurrent setting with the use of a MEKi, published in English. Case reports, case series, conference proceedings, in vitro studies and animal studies were excluded. Studies were screened and assessed for eligibility by two independent reviewers (AK, CC), with conflicts resolved by a third reviewer (TZ). Data was extracted using pre-established criteria. Results: The initial literature search identified 1815 papers; four met the eligibility criteria. Three were randomized clinical trials and one was a phase II single-arm prospective cohort study. MEKi investigated included: pimasertib, selumetinib, trametinib, and binimetinib. A total of 680 patients were included in these studies, of which 416 were treated with a MEKi alone. All patients were treated for recurrent LGSOC. Objective response rates (ORR) to MEKi ranged from 12.1 to 26% and median progression-free survival (PFS) ranged from 7.2 to 13 months. Conclusion: While one study demonstrated significantly improved efficacy of a MEKi over physician-choice systemic therapy in the treatment of recurrent LGSC, another did not show significant benefit. Two additional studies did not compare MEKi to current traditional chemotherapy or hormonal therapies used in the management of LGSC, limiting their clinical relevance. Mutation profiles within the tumors may affect the ORR to various MEKi. Further prospective and randomized trials are needed to determine the efficacy of MEKi in treating LGSC.